Optical transmittance and electric conductivity in nematic dispersions containing carbon nanotubes and organomodified montmorillonite - Minenko, S.S.; Kocherzhyn, A.I.; Lisetski, L.N.; Lebovka, N.I. (Functional Materials, 2009)
Optical transmission and electric conductivity were measured for dispersions of multiwalled carbon nanotubes (MWCNT), organomodified montmorillonite (MMT) and for hybrid dispersions of MWCNT+MMT in 5CB nematic liquid crystal (LC). The optical transmittance jump at the nematic-isotropic transition was observed in MMT+LC (~0.1 % wt. of MMT). This behaviour was qualitatively similar to that of reported earlier for MWCNT+LC (~0.1 % wt. of MWCNT) nanocomposites, suggesting exfoliation of the organoclay plate-like particles and their incorporation into the orientationally ordered nematic structure. In hybrid dispersions the effect of MWCNT and MMT on optical transmission was additive. Noticeable differences in the electric conductivity behaviour for composites filled with MWCNTs and organomodified MMT were observed. It was shown that MWCNTs facilitated and MMT hindered the electric field-induced transition from planar to homeotropic state in the LC cell. Досліджено оптичне пропускання та електропровідність дисперсій багатостінкових вуглецевих нанотрубок (НТ), органомодифікованого монтморилоніту (ММТ) та гібридних дисперсій НТ+ММТ у нематичному рідкому кристалі (РК) 5СВ. Спостерігали стрибок оптичного пропускання при нематико-ізотропному переході у ММТ+РК (~0.1 % ММТ). Така поведінка якісно подібна раніше описанії для нанокомпозитів НТ+ РК (~0.1 % НТ), що дозволяє припустити розшаровування пласких частинок органоглини та їх вбудовування в орієнтаційно впорядковану нематичну структуру. У гібридних дисперсіях вплив НТ та ММТ на оптичне пропускання був адитивним. Відзначено істотні відмінності у поведінці електропровідності між композитами, заповненими НТ та органомодифікованим ММТ. Показано, що НТ полегшують, а частинки ММТ утруднюють індукований електричним полем перехід від планарного до гомеотропного стану у рідкокристалічній комірці. Исследовано оптическое пропускание и электропроводность дисперсий многостеночных углеродных нанотрубок (НТ), органомодифицированного монтмориллонита (ММТ) и гибридных дисперсий НТ+ММТ в нематическом жидком кристалле (ЖК) 5СВ. Наблюдался скачок оптического пропускания при нематико-изотропном переходе в ММТ+ЖК (~0.1 % ММТ). Такое поведение качественно подобно ранее описанному для нанокомпозитов НТ+ЖК (~0.1 % НТ), что позволяет предположить расслаивание плоских частиц органоглины и их встраивание в ориентационно упорядоченную нематическую структуру. В гибридных дисперсиях влияние НТ и ММТ на оптическое пропускание аддитивно. Отмечены существенные различия в поведении электропроводности между композитами, заполненными НТ и органомодифицированным ММТ. Показано, что НТ облегчают, а частицы ММТ затрудняют индуцированный электрическим полем переход из планарного в гомеотропное состояние в жидкокристаллической ячейке.